A Study on the Role of Libraries In the Academic World: Evolution of Libraries and their Impact on Academic Research (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The library plays an important role in the academic worldby providing access to world class information resources and services, andstimulates academic research in the country. Access to information is not a newphenomenon but it exists through ages. Libraries being the centre forinformation storage and retrieval did exist from ancient times in one form orthe other. The libraries have transformed from museums to digital librariesover the time due to intervention of various technologies. The invention ofink, paper, printing technology and information and information communicationtechnologies (ICT) are the major technological milestones in the history oflibrary transformation. The printing technology helped the mass production ofbooks and other printed materials and brought them to the portal of library asprimary storage media.